Sistem Jaminan Lakang Wi,it di Kecamatan Talibura Kabupaten Sikka - Frederika Bernadeta Ursula Idam Putri; Maria Alfira Nata; Louisiano Grandiroyvan Wera Moa (Universitas Sains dan Teknologi Komputer, 2024)
The community of Talibura Subdistrict, Sikka Regency in carrying out economic activities has local wisdom which is often referred to as lakang wi,it which has been carried out by the Talibura subdistrict community for generations. Lakang Wi,it is an agreement made by a person with money to a person without money to do certain things within a certain time. In this research, the author wants to see the relationship between the Law of Association and also the local wisdom of Lakang Wi,it which both regulate agreements. This research is a sociological juridical legal research that has an object of study on community behavior. The law of engagement regulated in the Civil Code in force since the Dutch colonization of Indonesia has a relationship with the local wisdom of Lakang Wi,it in Talibura District, Sikka Regency. The similarity is that both regulate the agreement between the two parties and also lakang Wi,it is included in the form of an agreement in the form of an agreement that gives flexibility to both parties to enter into an agreement, the difference is that lakang wi,it is a small part of a broad and complete law of engagement while in local wisdom lakang Wi,it is more inclined to oral actions, not written and not as complete as the law of engagement in the Civil Code, in the settlement of disputes it is still thick with the customs of the local community.